Inhibition of HMG CoA Reductase and Lipid Peroxidation in The Rats Liver by Selected Zingiberaceae - Patonah Hasimun; Agus Sulaeman; Hendra Mahakam Putra; Heni Lindasari (Universitas Ahmad Dahlan, 2018)
Cardiovascular disease is the leading cause of death worldwide. One of the major risk factors for cardiovascular disease is hyperlipidemia. This study aimed to determine the potential of Zingiberaceae (10 species) as inhibitor of HMG-CoA reductase enzyme activity and lipid peroxidation. This study was conducted by 2 methods including assay of HMG CoA reductase inhibition and lipid peroxidation test. The study was performed by in vitro method, using 20% rat liver homogenate. The inhibition of HMG CoA reductase enzyme was done by reacting liver homogenate, HMG CoA substrate, which added the Zingiberaceae extract compared with simvastatin as standard drug. The absorbance of the mixture was measured by a Microlab 300 spectrophotometer at a 340 nm wavelength. Lipid peroxidation assay was induced by the FeSO4.7H2O solution. The absorbance value measured using a spectrophotometer at a 532 nm wavelength. Lipid peroxidation inhibition was characterized by absorbance of the test extract, compared with the control group. The obtained data was calculated as percent of inhibition and was used to calculate IC50 extract test. The results showed that the 10 ethanolic extracts of Zingiberaceae rhizomes have activity as enzyme inhibitor HMG-CoA reductase with IC50 value range 65.8±4.1 – 203.3±15.2 ppm, and inhibition of lipid peroxidation with IC50 value range 13.5±5.0 – 219.6±4.3 ppm. This study can be concluded that the Zingiberaceae rhizomes have potential role as antihyperlipidemic agents through inhibition of HMG CoA reductase enzyme activity and preventing lipid peroxidation.